The care of the common house in Boyacá. The responsibilities and challenges of the USTATunja with the environment (Quaestiones Disputatae: temas en debate, 2018)
The purpose of the manuscript is based on highlighting the thinking of the Catholic Church around the ﬁeld of "environment", in a historical development of recent times; John Paul II, Benedict XVI and Francis. In a special way, the thinking of Pope Francis is highlighted in the speeches delivered during his visits to Latin America (Colombia, Chile and Peru), where he convenes the future synod of the Amazonia. On the other hand, it is committed to the academic community, trying to make changes in the cultural and environmental perspective, as opposed to the responsibility of the Santo Tomás University in Tunja, making a "brief inventory" of the main difﬁculties surrounding the environment in the department of Boyacá.
Keywords: Ecology; Environmental Doctrine; Care of the Common House; Environmental Problem